Macrocyclic alkanes: A new class of biomarker - Audino, Michiele; Grice, Kliti; Alexander, Robert; Kagi, Robert (Pergamon-Elsevier, 2001)
A new class of cyclic hydrocarbon biomarker, macrocyclic-alkanes and their methylated analogues, have for the first time been unambiguously identified in a Botryococcus braunii rich sediment (torbanite).The compounds, consisting of a homologous series of macrocyclic-alkanes (ranging from C15 to C34) and their methylated derivatives (ranging from C17 to C26), were identified by using authentic standards and GC-MS techniques.